If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-9w + 2) + -9w + 2(w + -8) + -8 = 0 Reorder the terms: -3(2 + -9w) + -9w + 2(w + -8) + -8 = 0 (2 * -3 + -9w * -3) + -9w + 2(w + -8) + -8 = 0 (-6 + 27w) + -9w + 2(w + -8) + -8 = 0 Reorder the terms: -6 + 27w + -9w + 2(-8 + w) + -8 = 0 -6 + 27w + -9w + (-8 * 2 + w * 2) + -8 = 0 -6 + 27w + -9w + (-16 + 2w) + -8 = 0 Reorder the terms: -6 + -16 + -8 + 27w + -9w + 2w = 0 Combine like terms: -6 + -16 = -22 -22 + -8 + 27w + -9w + 2w = 0 Combine like terms: -22 + -8 = -30 -30 + 27w + -9w + 2w = 0 Combine like terms: 27w + -9w = 18w -30 + 18w + 2w = 0 Combine like terms: 18w + 2w = 20w -30 + 20w = 0 Solving -30 + 20w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 20w = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 20w = 0 + 30 20w = 0 + 30 Combine like terms: 0 + 30 = 30 20w = 30 Divide each side by '20'. w = 1.5 Simplifying w = 1.5
| X/2-7=7 | | 2500/y=500 | | 2x+2(5x+3)=74 | | x*2-9x=36 | | 2(5)+2(x)=40 | | 7x-3x+12=4x+6x | | 5/13 | | 2x+3-(-1+1x)=2x-2-x | | 5(3s+2m)= | | 8m-4(-5m+3)= | | (b-b^(1/3))/(b^(1/3)-1) | | y-3=-3(x+3) | | 4(x+2)-7=2x+2(-1+x) | | 11+8x-11-6x+6=11+(8x-11)-6x+6 | | 4(n-5)+15n=-4(-10n+3)-21n-8 | | 16=0 | | (x-3)x(x-5)= | | 5(3x-6)=9x-12 | | y-3=-3(x+3) | | y-3=-3(x-1) | | y+3=-3(x-3) | | k-16=-36 | | 4y+2=x | | -7t/2=7 | | y+3=-3(x+1) | | 3+2x-9=5x-21 | | 4xsquared+100=0 | | -3(5x+3)-2(x-6)= | | 1/2x2-3 | | c-79.9=-104.9 | | 3-3x=7x+12 | | w+6=57 |